Determine the frequency of peripartum hystrectomy in placenta previa - Usman, Amna; Shabbir, Quratulain; Naz, Falak; Yasmeen, Attiya; Naz, Mubashra; Faisal, Sanober (International Journal of Research in Medical Sciences, 2021)
Background: Peripartum hysterectomy is one of the life saving procedure performed after vaginal delivery or caesarean birth or in the immediate postpartum period in cases of intractable haemorrhage due to uterine atony, rupture uterus and placental disorders and it is usually reserved for the situations where conservative measures fail to control the haemorrhage. The objective of the study was to determine the frequency of peripartum hysterectomy in placenta praevia. Methods: The study was cross-sectional. It was conducted at the Department of Obstetrics and Gynaecology, Punjab Medical College and affiliated Hospital, Faisalabad. Study was carried out over a period of six months from October 2010 to March 2011. Total 130 cases of placenta praevia undergone caesarean section were included in this study. In cases of primary postpartum haemorrhage conservative management was done first in the form of intramuscular syntometrine (Oxytocin 5 IU/ergometrine 0.5 mg). Intravenous infusion syntocinon (40 IU in 500ml 0.9% saline over 4-6 hours). Results: Mean age of the patients was found to be 30.9±6.7 years. Distribution of cases by gestational age shows, 52 (40.0%) patients had gestation of 28-36 weeks and 78 (60.0%) patients had gestation of 37-41. Mean gestational age was observed 37.5±3.4 weeks. Parity distribution was as follows: 76 (58.5%) patients had parity 0-3, 34 (26.1%) patients had parity 4-6 and 20 (15.4%) patients had parity > 6 with mean parity of 3.2±1.9. Conservative management was done in 129 patients (99.3%). Peripartum hysterectomy was found to be in 1 patient (0.7%). Conclusions: Placental pathology is the leading cause of postpartum hemorrhage and the main indications of peripartum hysterectomy. Timely operation minimizes the morbidity and mortality.